Monetary policy and investment attractiveness of the national economy ("Journal "U". Economy. Management. Finance.", 2026)
The article examines the relationship between the monetary policy measures of the Bank of Russia and the dynamics of the national economy’s investment attractiveness in the context of a geopolitical shock. It analyses capital outflow channels and assesses the effectiveness of the regulator’s measures.
Keywords: monetary policy; investment attractiveness; key rate; foreign direct investment